Methodological Issues and Strategies in Clinical Research (4th Ed.).
DOI: 10.1037/14805-038
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for increasing replicability in psychology.

Abstract: Replicability of findings is at the heart of any empirical science. The aim of this article is to move the current replicability debate in psychology towards concrete recommendations for improvement. We focus on research practices but also offer guidelines for reviewers, editors, journal management, teachers, granting institutions, and university promotion committees, highlighting some of the emerging and existing practical solutions that can facilitate implementation of these recommendations. The challenges f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
165
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(176 citation statements)
references
References 31 publications
(40 reference statements)
8
165
0
Order By: Relevance
“…Pre-registration of the method of the research through peer review after which the journal guarantees publication irrespective of the outcome is expected to be effective to reduce QRPs of many sorts (e.g., Wagenmakers et al, 2012). Replication of research is often rightly advocated (Asendorpf et al, 2013a;Carpenter, 2012;Hartshorne & Schachner, 2012;Pashler & Wagenmakers, 2012;Yong, 2012), although one must realize that replication is most effective in controlled experiments done inside a lab. Exploration of one's data is a necessary research strategy in many research fields but may also invite accepting coincidental results that fail to be found in new data sets.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pre-registration of the method of the research through peer review after which the journal guarantees publication irrespective of the outcome is expected to be effective to reduce QRPs of many sorts (e.g., Wagenmakers et al, 2012). Replication of research is often rightly advocated (Asendorpf et al, 2013a;Carpenter, 2012;Hartshorne & Schachner, 2012;Pashler & Wagenmakers, 2012;Yong, 2012), although one must realize that replication is most effective in controlled experiments done inside a lab. Exploration of one's data is a necessary research strategy in many research fields but may also invite accepting coincidental results that fail to be found in new data sets.…”
Section: Resultsmentioning
confidence: 99%
“…One topic is to teach the importance and the technicalities of data management, including data collection, administration, storage, and publication and to try make students realize that data sharing can be highly productive. The other topic is to stimulate in students a heightened awareness of the importance of understanding how to use methodology and statistics well in data analysis (Asendorpf et al, 2013a), and often the key is to learn to recognize when one needs expert help.…”
Section: Consult a Methodsologist Or A Statisticianmentioning
confidence: 99%
See 3 more Smart Citations